Homework Help

What is the antiderivative of sin3x?

user profile pic

leeaeel | Student, Undergraduate | eNoter

Posted December 13, 2010 at 1:50 AM via web

dislike 1 like

What is the antiderivative of sin3x?

4 Answers | Add Yours

user profile pic

giorgiana1976 | College Teacher | Valedictorian

Posted December 13, 2010 at 1:53 AM (Answer #1)

dislike 1 like

To find the antiderivative of sin 3x, we'll have to determine the indefinite integral of sin 3x.

Int sin 3x dx

We'll substitute 3x by t.

3x = t

We'll differentiate both sides:

3dx = dt

We'll divide by 3:

dx = dt/3

We'll re-write the integral of the function , changing the variable x to t:

Int sin t*(dt/3) = (1/3)*Int sin t dt

(1/3)*Int sin t dt = - cos t/3 +C

We'll substitute t by 3x:

Int sin 3x dx =  - (cos 3x)/3 +C

user profile pic

hala718 | High School Teacher | (Level 1) Educator Emeritus

Posted December 13, 2010 at 1:56 AM (Answer #2)

dislike 1 like

Let f(x) = sin3x.

We need to find the anti-derivative of f(x).

Then, we need to find the integral of f(x).

==> intg f(x) = intg sin3x dx

   Let u = 3x ==> du = 3 dx

==> intg f(x) = intg sinu * du/3

                     = intg sin(u)/3  du

                     = (1/3) intg sinu du

                    = (1/3) * - cos(u) + C

Now we will substitute with u = 3x

==> intg f(x) = - (1/3) cos(3x) + C

                     = -cos(3x)/ 3  + C

user profile pic

justaguide | College Teacher | (Level 2) Distinguished Educator

Posted December 13, 2010 at 1:58 AM (Answer #3)

dislike 1 like

To find the integral of sin 3x we need to eliminate 3x.

Let us equate t = 3x

dt/dx = 3

=> dx = dt/3

Now substitute this in the given expression:

Int [ sin 3x dx] = Int [ (1/3)*sin t dt]

=> (1/3) (-cos t)  + C

substitute back t = 3x

=> (1/3) (-cos 3x) + C

Therefore integral of sin 3x is (1/3) (-cos 3x) + C.

user profile pic

neela | High School Teacher | Valedictorian

Posted December 13, 2010 at 2:00 AM (Answer #4)

dislike 1 like

To find the antiderivative of sin3x.

f(x) = sin3x.

Let 3x = t.

Differentiating 3x = t, we get 3dx = dt.

Therefore dx = dt/3.

Therefore Int f(x)dx = Int sint dt/3.

Int f(x) dx = (-cost)/3 +C....(1).

Now replace t = 3x in (1) and get:

Int f(x) dx = (-cos3x)/3 + C.

Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes